If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -9 = -3.64 Reorder the terms: -9 + g = -3.64 Solving -9 + g = -3.64 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + g = -3.64 + 9 Combine like terms: -9 + 9 = 0 0 + g = -3.64 + 9 g = -3.64 + 9 Combine like terms: -3.64 + 9 = 5.36 g = 5.36 Simplifying g = 5.36
| 2(5y+1)=-2(y-1)-48 | | 3x-y=12fory | | 11(3)+9=4(3)-30 | | -4x+7(-x+14)=197 | | -14+6b+7-2=1+5b | | s+2.52=19.49 | | 6x-7(6x-29)=-13 | | -180=n+816 | | 4x-2(x-5)=21x-9 | | 9-y=2y | | 17x+36=155 | | 2x^2+6x-94=0 | | 0=-16x^2+46x | | 3x+12y=15xy | | d+-951=-554 | | 91x^2+105x=-90 | | m*6*8:22=5/77*8 | | x^3-3x^2-4+12=0 | | 2x+8+4x+21+x-10=180 | | q-834=-65 | | (x+2)(x-3)-x(2x+1)+6x=0 | | 10(.5x+2)-5=3(x-6)+1 | | 14+3(6x-9)+12x=101 | | 6(7-2)= | | m*6=12 | | -6.5(2t+4)-1.2(4t-6)= | | 5f/10=f+2/6 | | g(x)=-2x^2-12x-14 | | g+-91=-75 | | 2x^2+18=54 | | 374=95x+75x | | n-8= 5 |